ANALYSIS OF ONLINE LEARNING OF HIGH SCHOOL STUDENTS IN CLASS X TARAKAN CITY - Zulfadli Zulfadli; Nuraini Nuraini (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
This study aims to determine the online learning process in high school students in Tarakan City. The type of research is qualitative with the subject of the study being high school students of class X. Data collection techniques used are observation, interviews, and documentation. The data analysis technique is the Miles and Huberman model, namely with data reduction, data presentation, and verification. The results of the research obtained that the learning process has run according to a predetermined schedule with the preparation of teachers in preparing learning tools such as Learning Implementation Plans (RPP), Use of Learning Media, and learning evaluation. However, during the implementation, there are several things that hinder the implementation of online learning such as the implementation process that does not run optimally due to an unstable internet network connection, task completion that does not run optimally, and some students do not have gadgets during the learning process